Invisible, but how? The depth of unconscious processing as inferred from different suppression techniques - Nathan Faivre (Frontiers Research Topics, 2015)
To what level are invisible stimuli processed by the brain in the absence of conscious awareness? It is widely accepted that simple visual properties of invisible stimuli are processed; however, the existence of higher-level unconscious processing (e.g., involving semantic or executive functions) remains a matter of debate. Several methodological factors may underlie the discrepancies found in the literature, such as different levels of conservativeness in the definition of "unconscious" or different dependent measures of unconscious processing. In this research topic, we are particularly interested in yet another factor: inherent differences in the amount of information let through by different suppression techniques. In the same conditions of well-controlled, conservatively established invisibility, can we show that some of the techniques in the "psychophysical magic" arsenal (e.g., masking, but also visual crowding, attentional blink, etc.) reliably lead to higher-level unconscious processing than others (e.g., interocular suppression)? Some authors have started investigating this question, using multiple techniques in similar settings . We argue that this approach should be extended and refined. Indeed, in order to delineate the frontiers of the unconscious mind using a contrastive method, one has to disentangle the limits attributable to unawareness itself, and those attributable to the technique inducing unawareness. The scope of this research topic is to provide a platform for scientists to contribute insights and further experiments addressing this fundamental question.